2022
DOI: 10.3389/fpls.2022.906071
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Salt Tolerance of Torreya grandis Genders Is Related to Nitric Oxide Level and Antioxidant Capacity

Abstract: Nitric oxide (NO), a bioactive molecule, is often involved in the regulation of physiological and biochemical processes in stressed plants. However, the effects of NO donors on dioecious plants remain unclear. Using a pot experiment, female and male Torreya grandis were used to study the role of sex and NO in salt stress tolerance. In the present study, female and male T. grandis seedlings pretreated with an NO donor (sodium nitroprusside, SNP) were exposed to salt stress, and then leaf relative water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
4
2
0
Order By: Relevance
“…The increase in ABS/RC in duckweed under SNP treatment can be explained by a decrease in the number of active reactive centers (RC) of PSII, which might serve as a defense mechanism to reduce the burden of its systems when stress occurs. These ndings are consistent with previous reports on torreya grandis [59]. The antenna proteins are essential for absorbing solar energy and for photoprotection in stressful situations [66].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in ABS/RC in duckweed under SNP treatment can be explained by a decrease in the number of active reactive centers (RC) of PSII, which might serve as a defense mechanism to reduce the burden of its systems when stress occurs. These ndings are consistent with previous reports on torreya grandis [59]. The antenna proteins are essential for absorbing solar energy and for photoprotection in stressful situations [66].…”
Section: Discussionsupporting
confidence: 93%
“…[58]. The ndings of this study showed that exogenous SNP caused the chlorophyll content of S. polyrhiza to decrease, and similar ndings were seen in other investigations, such as torreya grandis [59], chard [22] and syobean seedlings [60]. This may be due to the damage of photosynthetic pigments caused by SNP stress or the degradation of chlorophyll induced by NO [61].…”
Section: Discussionsupporting
confidence: 85%
“…The most significant photosynthetic pigment in plant chloroplasts is chlorophyll (Chl), which is crucial for absorbing light and transmitting light energy in antenna systems [ 56 ]. The findings of this study showed that SNP treatment caused the chlorophyll content of S. polyrrhiza to decrease, and similar findings were seen in other investigations, such as in Torreya grandis [ 57 ], chard [ 20 ] and soybean seedlings [ 58 ]. This may be due to the damage to photosynthetic pigments caused by SNP stress or the degradation of chlorophyll induced by NO [ 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…SOD first converts O ·-2 into H 2 O 2 and O 2 and then dissociates the generated H 2 O 2 and endogenous H 2 O 2 to stimulate POD and CAT activities, and the three synergistic processes eliminate excessive reactive oxygen species in plants ( Neto et al., 2006 ). Studies have found that shading, drought, salinity and other stresses can induce the activities of SOD, POD, CAT and other antioxidant enzymes and increase the ability of plants to remove reactive oxygen species, but this process is species-specific and varies with different stress types ( Favaretto et al., 2011 ; Bharuth et al., 2020 ; Liu et al., 2022 ). This study found that the activities of SOD, POD, CAT and APX in leaves of C. betulus first increased and then decreased with increasing shading intensity, but the activities of protective enzymes were higher than those of the control under different shading conditions.…”
Section: Discussionmentioning
confidence: 99%